PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS III DI UPT SD NEGERI 060794 MEDAN AREA TAHUN PEMBELAJARAN 2025/2026 - Saur Tua Van Mauricis Lumban Gaol; Juliana Panjaitan; Reflina Sinaga; Eka Kartika Silalahi; Paskah Sriulina Tarigan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the Contextual Teaching and Learning (CTL) model on Indonesian language learning outcomes, particularly on the topic of understanding the Subject-Predicate-Object-Adverbial (SPOK) sentence structure among third-grade students at UPT SD Negeri 060794 Medan Area in the 2025/2026 academic year. This research employed a quantitative approach using a One Group Pretest-Posttest Design. The sample consisted of 22 students selected through a saturated sampling technique. Data were collected through tests, questionnaires, and documentation. The research instruments were tested for validity and reliability before being used in the study. The results showed that the students’ mean pretest score of 50 increased to 79.09 on the posttest after the implementation of the CTL learning model. In addition, the questionnaire results regarding the implementation of the CTL model obtained an average score of 84.22, indicating a positive response from students toward the learning process. The correlation coefficient test yielded an r-value of 0.823, which was higher than the r-table value of 0.432, indicating a very strong relationship between the CTL model and students’ learning outcomes. Furthermore, the hypothesis testing (t-test) showed a significance value of 0.000 < 0.05 with a t-value of -9.542, leading to the rejection of H₀ and acceptance of H₁. Therefore, it can be concluded that the Contextual Teaching and Learning (CTL) model has a significant effect on the Indonesian language learning outcomes of third-grade students at UPT SD Negeri 060794 Medan Area, particularly in understanding SPOK sentence structures.